SANTAYANA, G. (2023). Winds of Doctrine: Studies in Contemporary Opinion. Cambridge (MA): MIT Press - Moreno Moreno, Daniel (Daimon Revista Internacional de Filosofia, 2025)
Reseña de SANTAYANA, G. (2023). Winds of Doctrine: Studies in Contemporary Opinion. Cambridge (MA): MIT Press.